Stretchable conductive fibers based on a cracking control strategy for wearable electronics - Zhang, Bo (2020)
Stretchability plays an important role in wearable devices. Repeated stretching often causes the conductivity dramatically decreasing due to the damage of the inner conductive layer, which is a fatal and undesirable issue in this field. Herein, a convenient rolling strategy to prepare conductive fibers with high stretchability based on a spiral structure is proposed. With the simple rolling design, low resistance change can be obtained due to confined elongation nof the gold thin-film cracks, which is caused by the encapsulated effect in such a structure. When the fiber is under 50% strain, the resistance change (R/R0) is about 1.5, which is much lower than a thin film at the same strain (R/R0 ≈ 10). The fiber can even afford a high load strain (up to 100%), but still retain good conductivity. Such a design further demonstrates its capability when it is used as a conductor to confirm signal transfer with low attenuation, which can also be woven into textile to fabricate wearable electronics.